Forrest Gump - Groom, Winston, 1944- (London : Penguin Books, 1996)
Through three turbulent decades, Forrest rides a tide of events that whisks him from physical disability to football stardom, from Vietnam hero to shrimp tycoon, from White House honors to the arms of his one true love.
5-8.
Pre-intermediate.
English.
Keywords: People with mental disabilities -- Fiction; Young men -- United States -- Fiction; Humorous fiction; Mentally handicapped -- Fiction; Young men -- Fiction; Humorous stories